Membangun Critical Thinking Pembelajaran di Era Digital - Fadillah, Ahmad Arif; Melyana, Angel; Anggraeni, Ani Nur; Afiyah, Azzahra Dhiya; Aprilia, Delia; Nuraeni, Eni; Amalya, Laura; Pratama, Riski; Hafidzoh, Siti; Wulandar, Sri (TSAQOFAH, 2022)
This study aims to find out how efforts can be made by educators or teachers in building critical thinking in learning in the current digital era and find out how important critical thinking is for every individual, especially in today's era in responding to the challenges of the industrial revolution. This research is a type of qualitative research using library research methods. Participation in this research was carried out by 9 students accompanied by 1 lecturer from the Muhammadiyah University of Tangerang. The results of our research sourced from articles and journals show that it is important to develop every individual who lives in the digital era to think critically. The role of teachers or educators in building critical thinking is very dominant. This is something that every educator should pay attention to in bringing up new innovations in the learning process to stimulate students in forming a critical mindset. Moreover, critical thinking is one of the abilities included in 21st century competencies that must always be built to face the challenges of the industrial revolution. , where the flow of information can come from anywhere, then the need for critical thinking skills is very useful for selecting relevant sources of information.